Hypophosphatemic Rickets: Presenting Features of Fanconi-Bickel Syndrome - Mahua Roy; K. Bose; D. K. Paul; Puja Anand (Hindawi Limited, 2011)
Fanconi-Bickel Syndrome (FBS) is a rare variety of glycogen storage disease (GSD). Characterized by massive hepatomegaly due to glycogen accumulation, severe hypophosphatemic rickets, and marked growth retardation due to proximal renal tubular dysfunction. We report a young boy presented as hypophosphatemic rickets with hepatomegaly and subsequently diagnosed as FBS.